PHYTOCHEMISTRY AND STUDY OF THE ANTIMICROBIAL ACTIVITY OF FRACTIONS OF THE HYDROETHANOLIC EXTRACT OF PUPALIA LAPPACEA (L.) JUSS (AMANRATHACEAE) - TOKOUDAGBA, Kossi Jean-Marie Denis; AHOUANSOU, AYIDE C. (My University, 2022)
Pupalia lappacea (Amanrathaceae) is a plant traditionally used in various ailments including febrile states and diarrhoea as a decoction and also in infertility. The control of bacterial infections is becoming complex due to the fact that many bacteria have developed resistance to most antibiotics, which is a major health problem worldwide. It is within this framework that we wanted to study the phytochemistry and the anti-microbial activity of the fractions of the hydro ethanolic extract of the plant used in traditional medicine it is Pupalialappacea (L.) JussAmanrathaceae We prepared the hydro ethanolic extract from the dried powdered leaves of these plants and the yield of crude extract is 20%. We then fractionated the hydro ethanolic extract obtained by the liquid-liquid extraction method using successively the following solvents of increasing polarity: cyclohexane, dichloromethane, ethyl acetate, and methanol. We measured flavonoids and polyphenols by the colorimetric method and the FolinCiocalteu method in these different fractions and then tested the hydroethanolic extract and the fractions on four reference microbial strains (Escherichia coli ATCC 25922 ; Salmonella typhi ATCC 14028 ; Staphylococcus aureus ATCC 25923 Pseudomonas aeruginosa ATCC 27853) The results showed us that the polar fractions are very rich in polyphenols which confirms the results obtained during the phytochemical screening carried out; and these fractions have a more interesting bactericidal activity than the hydro ethanolic extract. This plant could be an alternative in primary care systems for microbial infections.
Keywords: Pupalialappacea Bactericidal Concentration Minimum Inhibitory Concentration